The SAGE handbook of drug & alcohol studies / Biological approaches / edited by Kim Wolff, Jason White and Steven Karch - Wolff, Kim; White, Jason; Karch, Steven B. (The SAGE handbook of drug & alcohol studies, 2017)
With contributions from leading international academics across the social sciences, this accessible takes a critical look at the key contemporary issues and debates in the field. The 39 chapters are divided into three parts: Part I Central Social Science Theories Drug and Alcohol Studies Part II Pillars in Social Science Drug and Alcohol Studies Part III Controversies and New Approaches in Social Science Drug and Alcohol Studies This Handbook is an excellent reference text for the growing number of academics, students, scientists and practitioners in the drug and alcohol studies community.